2008
DOI: 10.1021/nl073356i
|View full text |Cite
|
Sign up to set email alerts
|

Control of Gold Surface Diffusion on Si Nanowires

Abstract: Silicon nanowires (NW) were grown by the vapor-liquid-solid mechanism using gold as the catalyst and silane as the precursor. Gold from the catalyst particle can diffuse over the wire sidewalls, resulting in gold clusters decorating the wire sidewalls. The presence or absence of gold clusters was observed either by high angle annular darkfield scanning transmission electron microscopy images or by scanning electron microscopy. We find that the gold surface diffusion can be controlled by two growth parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 22 publications
13
113
1
Order By: Relevance
“…It has been shown that these sidewalls correspond to {112} planes [9]. For <111>-oriented Si NWs grown by CVD at low silane partial pressure, that show similar sidewall orientations [10], gold is known to diffuse from the seed particle and to wet the sidewalls [11,12]. Adsorption of gold on Si(112) planes is also known to causes the faceting of these planes [13].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that these sidewalls correspond to {112} planes [9]. For <111>-oriented Si NWs grown by CVD at low silane partial pressure, that show similar sidewall orientations [10], gold is known to diffuse from the seed particle and to wet the sidewalls [11,12]. Adsorption of gold on Si(112) planes is also known to causes the faceting of these planes [13].…”
Section: Resultsmentioning
confidence: 99%
“…The migration of Au atoms from the catalyst at the top of the wire can be controlled by two crucial parameters, the partial pressure of SiH 4 and the growth temperature. The diffusion of Au atoms is suppressed when the partial pressure of SiH 4 is sufficiently high to permit gaseous SiH 4 to become adsorbed to the sidewall of the wire and when a relatively low growth temperature of 500 8C is used [12]. We first increased the growth temperature from 500 8C to 550 8C while maintaining the other parameters in order to limit Au diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, twin defect formation as well as the faceting phenomenon can be ascribed to the diffusion of Au. The Au atoms can diffuse along the sidewall of the wire from the Au tip during rapid wire growth and can be transformed into Au clusters in the solid-Si/liquid-Au state [12]. Formation of Au clusters on the wire surface is due to the surface tension required to form a droplet of liquid Au, which mainly occurs at the liquid/vapor interface.…”
Section: Resultsmentioning
confidence: 99%
“…Dayeh et al investigated the thermodynamics of Au diffusion along Ge nanowires using a Si layer to block this diffusion from the droplet of a Ge nanowire into the nanowire itself 181 . They estimated the lowest surface energy for a Au/Ge monolayer at the nanowire tip using a method outlined previously 182 , and expressed in equation…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%